1996
DOI: 10.1287/mnsc.42.6.830
|View full text |Cite
|
Sign up to set email alerts
|

Using the Deterministic EOQ Formula in Stochastic Inventory Control

Abstract: This note gives an improved bound (\root 5 - 2)/2 \approx 0.1180 for the relative cost increase when using the deterministic EOQ formula as a heuristic solution when demands are stochastic. We also discuss under what circumstances this bound is tight.inventory/production, lot sizing, error bound

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 4 publications
0
60
0
3
Order By: Relevance
“…Zheng (1992) has shown that the maximum relative error is bounded by 0.125. Axsater (1996) shows a slightly better bound of 0.118. Numerical experiments of practical situations show that the performance of this heuristic is usually much better than the worst-case bound.…”
Section: A Joint Location-inventory Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…Zheng (1992) has shown that the maximum relative error is bounded by 0.125. Axsater (1996) shows a slightly better bound of 0.118. Numerical experiments of practical situations show that the performance of this heuristic is usually much better than the worst-case bound.…”
Section: A Joint Location-inventory Modelmentioning
confidence: 96%
“…The retailers that are selected to operate as distribution centers (DCs) order inventory from the plant using an economic order quantity model (EOQ), which is an approximation to the Q r model with Type I Service constraint (Hopp andSpearman 1996, Nahmias 1997). Axsater (1996) points out that for Q r model, although it is, in general, relatively easy to derive the optimal solution, it is common in practice to use an approximate solution that is obtained in two steps. First the stochastic demand is replaced by its mean and the order quantity Q is determined by the deterministic EOQ formula.…”
Section: The Location Allocation Risk-pooling Modelmentioning
confidence: 99%
“…For example, interest has been devoted to analysing the size of errors incurred when replacing stochastic demand by its expected value in the model, e.g. (Zheng, 1992) and Axsäter (1996). Demand may be sequences of discrete demand events with variable size and in-between time intervals.…”
Section: Preface To the State Of The Artmentioning
confidence: 99%
“…This is probably because of two reasons. First, the total inventory cost has a very low sensitivity to inventory cost parameters (Axsäter, 1996). A second reason is the complexity of algebraic operations among random parameters with a probability distribution.…”
Section: Stochastic Modelsmentioning
confidence: 99%
“…Zheng (1992) demonstrates that the maximum relative error bound is 12.5%. Furthermore, Axsäter (1996) states that the increase is no more than 11.80%. Considering the cost and time required to develop inventory policies with more complex methodologies and software, we found that it is perfectly justified to take advantage of the simplicity of the deterministic EOQ formula even in stochastic situations.…”
Section: Deterministic Inventory Systemsmentioning
confidence: 99%